Interprofessional clinical placement involving speech pathology and counselling psychology - Ciccone, N.; Priddis, Lynn; Lloyd, A.; Hersh, D.; Taylor, A.; Standish, G. (The Speech Pathology Association of Australia Ltd., 2012)
This paper examines the interprofessional learning of a speech pathology and counselling psychology student in an interprofessional placement within an institution of the Department of Corrective Services in Perth, Western Australia. The institution is a pre-release centre that promotes rehabilitation and community reintegration in which up to six women are able to have their children, aged 0–4 years of age, live with them. The students provided a program to the mothers to facilitate development of a healthy mother–child relationship and the children’s communication development. This paper utilised qualitative descriptive analysis to explore two examples of student learning and found perceived growth in the students’ clinical skills, their understanding of the other profession and the concept of interprofessional collaboration. While students experience growth in a range of placements, the journey described in this paper is unusual in both the nature of the student collaboration and the placement itself. The research highlights the importance of joint clinical placements in the development of interprofessional collaborative relationships.